Practical Skills in Biomolecular Sciences - Reed, Rob (Robert H.) (Harlow : Pearson, 2013)
This is an easy-to-read guide to the principal techniques used in laboratory studies and data analysis used in biomolecular science - an indispensable practical aid for students who wish to succeed.
Previous ed.: Harlow: Prentice Hall, 2007.
Includes bibliographical references and index.
Keywords: Molecular biology -- Laboratory manuals; Science